2005
DOI: 10.1128/aem.71.12.8836-8845.2005
|View full text |Cite
|
Sign up to set email alerts
|

Community Analysis of a Mercury Hot Spring Supports Occurrence of Domain-Specific Forms of Mercuric Reductase

Abstract: Mercury is a redox-active heavy metal that reacts with active thiols and depletes cellular antioxidants. Active resistance to the mercuric ion is a widely distributed trait among bacteria and results from the action of mercuric reductase (MerA). Protein phylogenetic analysis of MerA in bacteria indicated the occurrence of a second distinctive form of MerA among the archaea, which lacked an N-terminal metal recruitment domain and a C-terminal active tyrosine. To assess the distribution of the forms of MerA in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…The S. solfataricus mer locus encodes four genes where merH, A and I are arranged in one transcription unit and merR is divergently transcribed upstream of merH. Protein phylogenetic analysis and gene disruption studies indicated that merA encoded a mercuric reductase required for reduction of mercuric ion, Hg(II), to its elemental form, Hg(0) (Schelert et al, 2004), despite its lack of an active tyrosine residue (Simbahan et al, 2005) in its putative active site. merI (122 aa) is located 39 to merA and is separated by a 142 nt intergenic region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. solfataricus mer locus encodes four genes where merH, A and I are arranged in one transcription unit and merR is divergently transcribed upstream of merH. Protein phylogenetic analysis and gene disruption studies indicated that merA encoded a mercuric reductase required for reduction of mercuric ion, Hg(II), to its elemental form, Hg(0) (Schelert et al, 2004), despite its lack of an active tyrosine residue (Simbahan et al, 2005) in its putative active site. merI (122 aa) is located 39 to merA and is separated by a 142 nt intergenic region.…”
Section: Introductionmentioning
confidence: 99%
“…The order Sulfolobales includes diverse thermoacidophilic microbes including species that inhabit hot metal-saturated locations (Orell et al, 2010;Simbahan et al, 2005;Wang et al, 2011). Studies on mercury resistance in Sulfolobus solfataricus established the existence and critical regulatory features of an archaeal mercury resistance (mer) operon Schelert et al, 2004Schelert et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…1). Protein phylogenetic analysis and gene disruption studies indicated that merA encodes a mercuric reductase required for reduction of the mercuric ion Hg(II) to its elemental Hg(0) form (Schelert et al, 2004) despite the lack of an active tyrosine residue (Simbahan et al, 2005) in the putative active site. merI (122 aa) is located 39 to merA and is separated by a 142 bp intergenic region.…”
Section: Introductionmentioning
confidence: 99%
“…The order Sulfolobales comprises diverse thermoacidophilic microbes, including species that inhabit hot metal-saturated locations (Simbahan et al, 2005). Studies on mercury resistance in Sulfolobus solfataricus established the existence and critical regulatory features of an archaeal mercury resistance (mer) operon Schelert et al, 2004Schelert et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Some operons also encode for the organomercury lyase and microbes carrying such mer operons reductively degrade MeHg (see above). The mer operon is broadly distributed among Bacteria and Archaea (Simbahan et al 2005) from diverse environments (Osborn et al 1997;Barkay et al 2010). The presence of Hg resistant bacteria in samples from polar environments (Møller et al 2011) and the demonstration of merA gene expression in samples from the High Arctic (Poulain, Ni Chadhain et al 2007) suggest that Hg resistant microbes may be endemic and active in cold regions, a conclusion that is also supported by the presence of mer gene homologs in the genomes of several psychrophilic bacteria from polar environments .…”
Section: Redox Transformations Of Inorganic Hgmentioning
confidence: 65%